2010
DOI: 10.1016/j.bpj.2009.10.013
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium Perchlorate Effects on the Helical Stability of a Mainly Alanine Peptide

Abstract: Sodium perchlorate salt (NaClO 4 ) is commonly used as an internal intensity standard in ultraviolet resonance Raman (UVRR) spectroscopy experiments. It is well known that NaClO 4 can have profound effects on peptide stability. The impact of NaClO 4 on protein stability in UVRR experiments has not yet been fully investigated. It is well known from experiment that protein stability is strongly affected by the solution composition (water, salts, osmolytes, etc.). Therefore, it is of the utmost importance to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 54 publications
(58 reference statements)
3
36
0
2
Order By: Relevance
“…In addition, Dzubiella used oligopeptides containing charged residues. In further work in progress using the AMBER force-field, 64 we were able to show that much longer peptides, comparable to those of Dzubiella, 29,30 or of Asciutto et al, 31 do in fact behave in an opposite way: they show decreased helicity in the presence of electrolytes. Since we believe that this major finding is robust and force-field independent, we have tried to understand its origin by a detailed energy analysis for all possible interactions in our systems.…”
Section: Conclusion and Perspectivementioning
confidence: 78%
“…In addition, Dzubiella used oligopeptides containing charged residues. In further work in progress using the AMBER force-field, 64 we were able to show that much longer peptides, comparable to those of Dzubiella, 29,30 or of Asciutto et al, 31 do in fact behave in an opposite way: they show decreased helicity in the presence of electrolytes. Since we believe that this major finding is robust and force-field independent, we have tried to understand its origin by a detailed energy analysis for all possible interactions in our systems.…”
Section: Conclusion and Perspectivementioning
confidence: 78%
“…The ions seem to have multiple effects including ion-specific interactions with proteins, polymers, and solvation waters [4,20]. Multiple studies have shown ion-specific interactions with amino acids, the peptide backbone, and solvation water alter protein structures [21][22][23][24][25][26]. Recently, infrared spectroscopy has been shown to be a useful technique to study differences in peptide and polymer solvation [27].…”
Section: Introductionmentioning
confidence: 99%
“…which is the GK relation (9). Since for large t the second integral on the right relaxes to the fixed value more slowly, the diffusion coefficient calculated using MSD and velocity ACF is the same for very long simulation times.…”
Section: Simulationsmentioning
confidence: 78%
“…Although its water solutions are commonly used in many practical applications, e.g. as supporting electrolytes in electrochemical studies, there are only few papers related to NaClO 4 in water [3][4][5][6][7][8][9][10]. In this paper the recent results of shear viscosity, diffusion coefficients and conductivity calculations applying molecular dynamics simulations for different NaClO 4 concentrations in tip3p and tip4p/2005 water models are presented.…”
Section: Introductionmentioning
confidence: 99%